13.7k views
4 votes

2 \sin( \alpha ) - \cos( \alpha ) = 2 \\

find the value of:

\sin( \alpha ) + 2 \cos( \alpha )


1 Answer

2 votes


2\sin\alpha-\cos\alpha=2

Consider the substitution
\tan\frac\alpha2=\beta. Then by the double angle identities we get


\sin\alpha=2\sin\frac\alpha2\cos\frac\alpha2


\cos\alpha=\cos^2\frac\alpha2-\sin^2\frac\alpha2

We also have


\tan\frac\alpha2=\beta\implies\begin{cases}\sin\frac\alpha2=\frac\beta{√(1+\beta^2)}\\\\\cos\frac\alpha2=\frac1{√(1+\beta^2)}\end{cases}

so that


\sin\alpha=(2\beta^2)/(1+\beta^2)


\cos\alpha=(1-\beta^2)/(1+\beta^2)

and the original equation has been transformed to


(4\beta^2-(1-\beta^2))/(1+\beta^2)=2

Solve for
\beta:


5\beta^2-1=2+2\beta^2


3\beta^2=3


\beta^2=1


\beta=\pm1

Solving for
\alpha gives


\tan\frac\alpha2=-1\implies\frac\alpha2=-\frac\pi4+n\pi\implies\alpha=-\frac\pi2+2n\pi


\tan\frac\alpha2=1\implies\frac\alpha2=\frac\pi4+n\pi\implies\alpha=\frac\pi2+2n\pi

where
n is any integer. Both
\sin and
\cos are
2\pi-periodic, which is to say


\cos(x+2n\pi)=\cos x


\sin(x+2n\pi)=\sin x

so that


\sin\alpha=\sin\left(\pm\frac\pi2+2n\pi\right)=\sin\left(\pm\frac\pi2\right)=\pm1


\cos\alpha=\cos\left(\pm\frac\pi2+2n\pi\right)=\cos\left(\pm\frac\pi2\right)=0

and we find that


\sin\alpha+2\cos\alpha=\pm1

User Freddoo
by
4.6k points